2021
DOI: 10.1038/s41598-021-85104-w
|View full text |Cite
|
Sign up to set email alerts
|

Canine mammary cancer tumour behaviour and patient survival time are associated with collagen fibre characteristics

Abstract: Precise diagnosis and prognosis are key in prevention and reduction of morbidity and mortality in all types of cancers. Here we show that changes in the collagen fibres in the main histological subtypes of canine mammary gland carcinomas are directly associated with the tumour behaviour and the animal survival time and could become a useful tool in helping with diagnosis. Imaging by second harmonic generation and multiphoton excited fluorescence microscopy were performed to evaluate the collagen and cellular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 62 publications
1
18
0
5
Order By: Relevance
“…Its fibers have been reported as biomarkers of pulmonary metastasis in murine models with mammary gland tumors (Provenzano et al, 2008). The lack of a defined boundary between tumor-stroma and the width of the collagen fiber is associated with a decrease in patient survival considering related factors such as tumor grade (Case et al, 2017), also is related that the more aggressive carcinomas present shorter collagen fibers in comparison with the less aggressive (Garcia et al, 2021). At the genetic level, analysis of stromal mRNA level in normal and tumoral mammary tissue indicated that genes coding for Coll-I, fibroblast activation protein, and α-smooth muscle actin are highly expressed in tumor stroma than in normal tissues (Ettlin et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its fibers have been reported as biomarkers of pulmonary metastasis in murine models with mammary gland tumors (Provenzano et al, 2008). The lack of a defined boundary between tumor-stroma and the width of the collagen fiber is associated with a decrease in patient survival considering related factors such as tumor grade (Case et al, 2017), also is related that the more aggressive carcinomas present shorter collagen fibers in comparison with the less aggressive (Garcia et al, 2021). At the genetic level, analysis of stromal mRNA level in normal and tumoral mammary tissue indicated that genes coding for Coll-I, fibroblast activation protein, and α-smooth muscle actin are highly expressed in tumor stroma than in normal tissues (Ettlin et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The collagen plays a crucial role in modulating the biological behavior of CMTs, and there is evidence that tumorassociated collagen signatures (TACS) defined by secondgeneration harmonic imaging (SHG) that are predictive of aggressive biologically behavior and poor prognosis (Case et al, 2017;Garcia et al, 2021). Picrosirius (PSR) is a stain that highlights the collagen present in the stroma of the tissues employing the birefringence of the collagen fibers, detected under polarized light (Rittié, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that higher intratumoral collagen levels are associated with lower-grade canine cutaneous mast cell tumors, with greater survival times in those with a value lower than 9.25% [29,32]. In female dogs with mammary tumors, aggressive carcinomas with shorter collagen fibers are present, which directly affects the survival time [34]. This has also been observed in feline mammary tumors, in which denser collagen, thicker and straighter fibers, and less-identifiable tumor-stromal boundaries are associated with poorer outcomes, independent of the clinical variables, thus increasing the predictive power of the clinical model [35].…”
Section: Discussionmentioning
confidence: 99%
“…Compounds that inhibit the adhesion of tumor cells to the ECM have also been shown to prevent metastasis [33]. Aggressive carcinomas with shorter collagen fibers are present in female dogs with mammary tumors, which directly affects survival time [34]. This has also been observed in feline mammary tumors, wherein denser collagen, thicker and straighter fibers, and less identifiable tumor-stromal boundaries are associated with poorer outcomes, independent of clinical variables, thus increasing the predictive power of the clinical model [35].…”
Section: Introductionmentioning
confidence: 99%
“…Embora não esteja incluída nos critérios da graduação elaborados por Elston e Elis (1991) para os carcinomas mamários, esta lesão é considerada uma importante característica de malignidade na avaliação histopatológica de diversos tumores, incluindo as neoplasias mamárias (Goldschmidt et al, 2011;Zappulli et al,2019) Garcia et al, (2021), onde foi observado maior proporção de fibras de colágeno mais curtas em carcinomas mamários invasivos e que foram relacionados à menor taxa de sobrevida em cadelas. Outros estudos com a avaliação do colágeno em neoplasias malignas de cães também observaram alterações nas fibras colágenas semelhantes com as encontradas no presente estudo (Bedoya et al, 2016;Martins et al, 2002).…”
Section: Análise Histopatológicaunclassified